Epidermal hydration levels in patients with rosacea improve after minocycline therapy. (1st August 2014) - Ní Raghallaigh, S.; Powell, F.C.
Summary: Background: Patients with rosacea frequently report increased skin sensitivity, with features suggestive of an abnormal stratum corneum (SC) permeability barrier. Sebum, pH and hydration levels influence epidermal homeostasis. The correlation of changes in these parameters with clinically effective treatment has not been previously analysed. Objectives: To analyse sebum, pH and epidermal hydration levels of patients with papulopustular rosacea (PPR) before and after treatment with systemic minocycline. Methods: We analysed sebum casual levels, pH and hydration along with erythema levels (as a marker of disease activity and response to treatment) on seven designated facial sites of 35 patients with active PPR and compared the results with values on the same sites of 34 control subjects with normal facial skin. To determine the effect of minocycline on these parameters, we re‐examined the patients with PPR at the same sites after a 6‐week course of treatment. Results: Patients with untreated PPR had significantly increased erythema indices, normal sebum casual levels, a more alkaline centrofacial region and reduced epidermal hydration levels compared with controls. Treatment with minocycline resulted in reduced erythema and increased hydration levels, with the most marked changes evident in the cheeks (13·3% reduction in erythema indices, P < 0·001; 12·4% increase in hydration levels, P = 0·012). There was no change in skin pH or sebum casual levels following treatment. Conclusion: Patients with PPR have increased erythema indices, normal sebum casual levels, a more alkaline centrofacial region and reduced epidermal hydration levels compared with control subjects. Treatment with systemic minocycline reduces erythema and increases hydration, in the absence of any change in skin pH or sebum casual levels.